Scenes and Communities in the City - Klekotko, Marta (Springer Nature, 2024)
​This open access book addresses the problem of creation and reproduction processes of contemporary urban communities, as well as cultural mechanisms and factors of these processes. Rejecting both the environmental determinism, and cultural reductionism of community studies, the book assumes that the postmodern city is a space of diverse urban communities that go far beyond the traditional concept of neighbourhood as well as personal and imagined communities, and thus proposes to comprehend urban community as social practice embedded in urban space. The book applies the Theory of Social Practice and the Theory of Scenes and develops the concept of socio-cultural opportunity structures in order to explain how cultural practices of individuals and symbolic dimensions of territory interact, leading to (re)production of various forms of urban community. It is assumed that culture in general and symbolic meanings of territory in particular, play a crucial role in the process of (re)production of urban communities, that this process takes place in collective cultural consciousness and is mediated by territorially embedded cultural practices of individuals. The book overcomes theoretical gaps in classical community studies and develops a new perspective on urban communal processes based on the analysis of social practices in urban cultural scenes.